A direct sensitivity comparison between flow‐modulated comprehensive 2D and 1D GC in untargeted and targeted MS‐based experiments. Issue 17 (19th July 2013) - Tranchida, Peter Q.; Franchina, Flavio A.; Zoccali, Mariosimone; Bonaccorsi, Ivana; Cacciola, Francesco; Mondello, Luigi; Svec, Frantisek
<x xml:space="preserve">Abstract</x> The present contribution is focused on the measurement of the analytical sensitivity attained in untargeted/targeted MS/MS experiments, performed using flow‐modulator comprehensive 2D and 1D GC. The comprehensive 2D experiment was performed by diverting part of the high flow (circa 80%) to flush the accumulation loop (about 28 mL/min) to waste, to reduce the gas flow entering the ion source. 1D analyses were performed through: (i) unmodulated and (ii) single column applications. An equivalent temperature program was applied in the modulated and unmodulated analyses, while a faster one was employed in the single column one. In all application types, the (same) triple quadrupole instrument was operated in the full‐scan and multiple reaction monitoring modes. A genuine sweet orange oil and the same sample spiked with 20 phytosanitary compounds were employed to reach the research objective. The results highlight the problems related to the flow modulation–MS combination. Specifically, it was found that sensitivity was on average three to four times higher in unmodulated and optimized single‐column applications.